2016
DOI: 10.3390/rs8100849
|View full text |Cite
|
Sign up to set email alerts
|

Landsat and Local Land Surface Temperatures in a Heterogeneous Terrain Compared to MODIS Values

Abstract: Land Surface Temperature (LST) as provided by remote sensing onboard satellites is a key parameter for a number of applications in Earth System studies, such as numerical modelling or regional estimation of surface energy and water fluxes. In the case of Moderate Resolution Imaging Spectroradiometer (MODIS) onboard Terra or Aqua, pixels have resolutions near 1 km 2 , LST values being an average of the real subpixel variability of LST, which can be significant for heterogeneous terrain. Here, we use Landsat 7 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Azeñas et al () have recently shown in a study for the same location that under sunny conditions vegetated areas are very efficient in removing water from the upper soil leading to very dry surfaces that may be hotter in the day and colder at night than the surrounding less vegetated areas. The spatial variability for an instant either at day or at night is in the range of 10 to 15 °C, as found by Simó et al (). Contrarily to T2m, for Tsoil the morning and evening transitions do not take place simultaneously at all poles, each surface reacting differently to the appearance and disappearance of the solar radiation.…”
Section: Spatial Variability Of Air and Soil Variablessupporting
confidence: 73%
See 2 more Smart Citations
“…Azeñas et al () have recently shown in a study for the same location that under sunny conditions vegetated areas are very efficient in removing water from the upper soil leading to very dry surfaces that may be hotter in the day and colder at night than the surrounding less vegetated areas. The spatial variability for an instant either at day or at night is in the range of 10 to 15 °C, as found by Simó et al (). Contrarily to T2m, for Tsoil the morning and evening transitions do not take place simultaneously at all poles, each surface reacting differently to the appearance and disappearance of the solar radiation.…”
Section: Spatial Variability Of Air and Soil Variablessupporting
confidence: 73%
“…Simó et al () recently analyzed the land surface temperature (LST) heterogeneities in the Campus using Landsat‐7 ETM data and found that the variability was in the range 5 to 15 °C depending on the season. These results allowed to determine locations in the Campus to deploy nine instrumented poles in different types of terrain representative of the surface variability of the 1‐km side study area.…”
Section: Site and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Since more than 95% of the surface inside this square is wild grass vegetation, which was the same observed surface from the IR120 broadband radiometer, and a circular geolocation error uncertainty requirement of 12 m is assumed for both the reflective and emitted radiance data [3], it was presumed that both the IR120 and L8-TIRS LST estimations are comparable. Recent studies have also validated the LST estimated from several orbiting TIR sensors against data from this SEB station, concluding that with respect to in situ temperature field measurements, the LST obtained from Landsat 7-ETM + showed a RMSE of ±1.7-1.8 K and, for the Terra-ASTER, a RMSE of ±1.3 K [16,17].…”
Section: Study Sitementioning
confidence: 62%
“…Secondly, different resolutions between ground observation and satellite-derived data might introduce uncertainties in the correlation analysis between climate and vegetation indices at the site scale. Simó et al [74] indicated that there is a bias between in situ data and satellite-derived pixel average in a heterogeneous area. Thirdly, other factors may also influence ecosystems, such as CO 2 fertilization effects [9], nitrogen deposition and interference from human activities (e.g., land cover change) [75].…”
Section: Uncertainties and Perspectivesmentioning
confidence: 99%